2011
DOI: 10.1038/mt.2011.219
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety of RNAi-Mediated HTT Suppression in the Rhesus Macaque as a Potential Therapy for Huntington's Disease

Abstract: To date, a therapy for Huntington's disease (HD), a genetic, neurodegenerative disorder, remains elusive. HD is characterized by cell loss in the basal ganglia, with particular damage to the putamen, an area of the brain responsible for initiating and refining motor movements. Consequently, patients exhibit a hyperkinetic movement disorder. RNA interference (RNAi) offers therapeutic potential for this disorder by reducing the expression of HTT, the disease-causing gene. We have previously demonstrated that par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
185
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(190 citation statements)
references
References 47 publications
5
185
0
Order By: Relevance
“…Although this technique could be very powerful, mutant-selective RNAi depends on targeting single nucleotide or deletion polymorphisms that differentiate between alleles, and these often differ from patient to patient. However, there is evidence that partial repression of wt HTT can be tolerated (14,15), suggesting that generic approaches that repress both alleles should also be pursued. Peptide nucleic acids and locked nucleic acids are generic; yet, some promising partially selective inhibition of expanded CAG repeats of the ataxin-3 and HTT genes has been reported (16,17).…”
mentioning
confidence: 99%
“…Although this technique could be very powerful, mutant-selective RNAi depends on targeting single nucleotide or deletion polymorphisms that differentiate between alleles, and these often differ from patient to patient. However, there is evidence that partial repression of wt HTT can be tolerated (14,15), suggesting that generic approaches that repress both alleles should also be pursued. Peptide nucleic acids and locked nucleic acids are generic; yet, some promising partially selective inhibition of expanded CAG repeats of the ataxin-3 and HTT genes has been reported (16,17).…”
mentioning
confidence: 99%
“…Both nonallele-specific (targeting the mutant and wild type alleles) and allele-specific (targeting only the mutant allele) approaches for HD therapy are under development. It has been shown recently that nonallele-specific silencing, using AAVmediated delivery of RNAi, provides benefits in a mouse model of HD and 2 studies assessing the effect of knockdown of endogenous HTT in rhesus found no adverse effects up to 6 months post-injection [81,82]. However, HTT is necessary for embryonic development and is involved in cellular pathways in differentiated neurons [83][84][85][86][87][88].…”
Section: Huntington's Diseasementioning
confidence: 99%
“…For example, SCA1, SCA2, and SCA3 knockout mice are viable and fertile, indicating that knockdown of the wild type allele function may be tolerable [96,166,167]. Nonallele-specific silencing of HTT in HD mice resulted in a significant rescue of the HD phenotype, and 2 studies have shown that reducing levels of wild type HTT in the adult rhesus macaque striatum is safe and well tolerated for at least 6 months [80][81][82]. However, as the HD null mice are embryonic lethal, and the levels of HTT required for cell viability of adult neurons is unknown, researchers are also investigating allele-specific silencing options [83].…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations